PEMBUATAN VIDEO TUTORIAL STRATEGI BERTAHAN DAN MENYERANG DALAM PERMAINAN BOLA BASKET - Gledis Emanuela; Fitri Dwi Kartikasari; Hendra Dinata (Perpustakaan Universitas Surabaya, 2018)
Basketball is a team of five people. In basketball matches required compactness between players. If when surviving and attacking from five people only one person who mastered the technique, then not necessarily the team will win. Therefore, one team must master both defense and attack techniques in playing basketball. This is the background of making this video tutorial application. This app is called “Tutorial Menyerang dan Bertahan Permainan Bola Basket”, where this app aims to help understand the techniques of survival and attack basketball. This application was created using Adobe Illustrator CS6 software, Adobe After Effects CC and Adobe Flash Professional CS6. This app contains about defense and assault. Defense is an effort run by a defensive team in order to dispel an opponent's attack. In addition to defensive techniques, players must also master the attacking techniques in basketball games. Assault is an effort run by an attacking team in order to score numbers into a basketball ring. Verification and validation resultsnote that this application has been running smoothly. Based on the results of 20 people, 10% of respondents said agree and 90% said strongly agree that this application can provide knowledge to understand the techniques of survival and attack basketball. In addition, respondents considered this app already has an attractive visual appearance and an easy to understand interface.